SIE BOEN LIAN (SBL) SURGICAL TECHNIQUE FOR CICATRICIAL ENTROPION AFTER STEVENS-JOHNSON SYNDROME: Poster Presentation - Case Report - Resident - GEORGE RADEN MAS SAID; Niluh Putu Ayu Dewi Wardhani; Raden Rangga Kartiwa; Shanti Fitriani Boesoirie; Mohamed Rinaldi Dahlan (Majalah Oftalmologi Indonesia, 2023)
Introduction : Stevens-Johnson Syndrome (SJS) can cause keratinization of the tarsal conjunctiva, conjunctival scarring and inverted eyelid margin, resulting to cicatricial entropion, causing skin and lashes to brush against the eye. This condition can occur in 27-59% of cases in ocular SJS. The surgical treatment for cicatricial entropion is to repair the position of eyelid margin. One of the procedures that can be used is Sie Boen Lian (SBL) technique. Case Illustration : A 70-year-old woman complained of inversion of the left upper eyelid, which caused foreign body sensation, redness, and lacrimation since 4 months ago. The patient had a history of SJS caused by the use of quinolone antibiotic. Anterior segment examination revealed entropion in the left upper eyelid with palpebral margin keratinizing. The patient was diagnosed with cicatricial entropion post- SJS. SBL surgical technique was chose to manage this condition. Post-operative ophthalmological examination showed a relieved symptoms and an improvement in the position of the eyelid margin. Discussion : The primary goal of therapy in cicatricial entropion is to reduce the occurrence of chronic ocular irritation by reverting the structure of the eyelids to a physiological position. The anterior lamellar shortening was performed with a modified tarsotomy, known as the SBL surgical technique. The post-operative evaluation was implemented to assess the reposition of the eyelid margin. Conclusion : The SBL surgical procedure is effective to manage cicatricial entropion post-Steven-Johnson Syndrome.